Antonin Artaud - Murray, Ros. author. aut Link
XIII, 190 p.
Keywords: This book serves as analysis of the aesthetics of materiality in the multifaceted work of Antonin Artaud, one of Twentieth-Century France's most provocative and influential figures, spanning literature, performance, art, cinema, media and critical theory.